Penerapan Metode AHP Dalam Mencari Jurusan Yang Paling Diminati - Narti Narti; Ahmad Yani; Sriyadi Sriyadi (Evolusi : Jurnal Sains dan Manajemen, 2020)
AbstractThe availability of a choice of majors in SMA makes various motivations and the basic reasons for students to choose and take the study program they will study later. This research was made in order to know the appropriate study program / department in the consideration of students in terms of the students' basic reasons for choosing a major. The research was conducted by distributing questionnaires to 41 respondents, and the model used was the AHP (Analytical Hierarchy Process) model, which is a multicriteria decision-making method. With this research, it is expected that there will be a change in the mindset of students in choosing the department so that they are not wrong in determining the chosen department. The results showed that there were three main criteria used, namely Interest, Role of Parents and Opportunities, where it was found that interest was the highest criterion in the selection of a department, namely 47% or 0.47 and in the process of selecting the Department there were three alternatives, namely Accounting, Multimedia, and Computer and Network Engineering that produces accounting as the most important alternative with the highest priority weight of 37% or 0.37.  Keywords: AHP method; Search for majors AbstrakTersedianya pilihan jurusan di SMA membuat beragam motivasi serta alasan dasar dari siswa dalam memilih dan mengambil program studi yang nanti dipelajarinya. Penelitian ini dibuat agar diketahuinya program studi/ jurusan yang sesuai pada pertimbangan siswa yang ditinjau dari alasan dasar siswa dalam memilih jurusan. Penelitian dilakukan dengan cara penyebaran kuesioner ke 41 responden, dan model yang digunakan adalah model AHP (Analytical Hierarchy Process) yang merupakan sebuah metode pengambilan keputusan multikriteria. Dengan penelitian ini diharapkan adanya perubahan pola pikir siswa dalam memilih Jurusan agar tidak salah dalam menentukan Jurusan yang dipilih. Hasil penelitian menunjukkan ada tiga kriteria utama yang digunakan yaitu Minat, Peran Orang Tua dan Peluang, dimana didapatkan bahwa Minat menjadi kriteria tertinggi pada pemilihan Jurusan yaitu 47% atau sebesar 0,47 serta dalam proses pemilihan Jurusan terdapat tiga alternatif yaitu Akuntansi, Multimedia, serta Teknik Komputer dan Jaringan yang menghasilkan Akuntansi sebagai alternatif terpenting dengan bobot prioritas tertinggi 37% atau sebesar yaitu 0,37. Kata Kunci: Metode AHP; Mencari Jurusan